2019
DOI: 10.1111/jcmm.14796
|View full text |Cite
|
Sign up to set email alerts
|

CYP2J2/EET reduces vulnerability to atrial fibrillation in chronic pressure overload mice

Abstract: Growing evidence has well established the protective effects of CYP2J2/EET on the cardiovascular system. The aim of the present study was to determine whether CYP2J2/EET has a preventive effect on atrial fibrillation (AF) and to investigate the underlying mechanisms. Wild‐type mice were injected with or without AAV9‐CYP2J2 before abdominal aortic constriction (AAC) operation. After 8 weeks, compared with wild‐type mice, AAC mice display higher AF inducibility and longer AF durations, which were remarkably atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…It was proven that the TGF-β/Smad pathway was involved in the process ( Li et al, 2020a ). They also found that similar effects were observed in the abdominal aortic constriction model, which is another pressure overload-induced cardiac remodeling model ( Li et al, 2020b ). Besides, Ang II-induced cardiac remodeling is always accompanied by cardiac fibrosis.…”
Section: The Role Of Eets In the Pathological Changes Of Cardiac Remosupporting
confidence: 53%
“…It was proven that the TGF-β/Smad pathway was involved in the process ( Li et al, 2020a ). They also found that similar effects were observed in the abdominal aortic constriction model, which is another pressure overload-induced cardiac remodeling model ( Li et al, 2020b ). Besides, Ang II-induced cardiac remodeling is always accompanied by cardiac fibrosis.…”
Section: The Role Of Eets In the Pathological Changes Of Cardiac Remosupporting
confidence: 53%
“…Cytochrome P450 epoxygenase 2J2 (CYP2J2) is widely expressed in cardiac myocytes, vascular endothelium, the liver, and the pancreas in humans and is required for arachidonic acid metabolism. CYP2J2 converts arachidonic acid to four regioisomeric epoxyeicosatrienoic acids (5,6‐EET; 8,9‐EET; 11,12‐EET; and 14,15‐EET) 27 . As reported, CYP2J2 and its lipid metabolites exert beneficial effects on diabetes, cardiovascular dysfunction, and central nervous diseases.…”
Section: Introductionmentioning
confidence: 81%
“…CYP2J2 converts arachidonic acid to four regioisomeric epoxyeicosatrienoic acids (5,6-EET; 8,9-EET; 11,12-EET; and 14,15-EET). 27 As reported, CYP2J2 and its lipid metabolites exert beneficial effects on diabetes, cardiovascular dysfunction, and central nervous diseases. Yan Yang et al demonstrated that CYP2J2 overexpression attenuated age-related insulin resistance.…”
mentioning
confidence: 90%
“…Supportive investigations determining the effects of EETs in vascular inflammation demonstrated intra-arterial perfusion of 11,12-EET decreased endothelial VCAM-1 expression and prevented the adhesion of mononuclear cells in mice following injection of TNF-α [ 219 ]. Moreover, the increase in EET levels associated with the cardiac specific overexpression of CYP2J2-attenuated atrial fibrosis and inflammatory responses in a mouse model of atrial fibrillation induced by constriction of the abdominal aorta [ 221 ]. Treatment with EET analogs limited myocardial fibrosis and macrophage infiltration, decelerating the progression of MI-induced HF in rats subjected to ligation of left anterior descending (LAD) coronary artery [ 192 ].…”
Section: Anti-inflammatory Effects Of N-3 and N-6 Pufa-derived Epomentioning
confidence: 99%